INVENTARISASI DAN PEMBARUAN KOMPOSISI SPESIES IKAN DI SUNGAI BUMANG, PULAU BANGKA - Uswatun; Reza; Ali Akbar, Muhammad; Kurniawan, Ardiansyah (Universitas Cokroaminoto Palopo, 2025)
The Bumang River is one of the rivers on Bangka Island that has not been affected by tin mining. Several fish species have been reported in this river, including Osteochilus spilurus, Pristolepis grooti and Brevibora cheeya. This study aims to inventory and re-update the composition of fish species in the Bumang River, Bangka Island. Exploration and identification of freshwater fish were carried out in June - August 2025. The location of the fish exploration in the Bumang River is in Kemuja Village, West Mendo District, Bangka Regency with coordinates 2 ° 5′ 8.48 ″ S, 105 ° 57′ 24.55 ″ E. This study uses a descriptive exploratory. Exploration of fish samples from several points in the river using umbrella traps. The fish obtained will be identified and water quality measurements will be carried out directly in the waters where the traps are installed. A total of 37 species and 7 families of fish were collected during the research. Among the seven families identified, the Cyprinidae family had the largest number of species, with 12, followed by the Osphronemidae family with 7 species, and the remaining families with only 1 to 3 species. The high number of species and families identified indicates that the Bumang River has a high fish diversity and the diversity of fish in this river is also enriched by the presence of endemic species, namely: Betta schaleri, Betta chloropharynx, and Parospremenus bintan.